2013
DOI: 10.1007/s10517-013-2241-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Rhenium Cluster Complex K4[Re6S8(CN)6] in the Body of Laboratory Rats

Abstract: We studied the biodistribution of luminescent octahedral rhenium cluster complex K4[Re6S8(CN)6], a promising agent for photodynamic therapy. It was shown that rhenium complex [Re6S8(CN)6](4-)is mainly accumulated in the liver, the central organ of metabolism, and can be excreted by the kidneys. The cluster complex was also accumulated in the spleen in significant amount, which makes it a promising agent for creation of preparations for diagnostics and treatment of lymphoproliferative disorders. The mean lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is clear that the cluster complex excreted through the kidneys rapidly. Earlier, we have demonstrated that cluster complex 1 can also be excreted through the kidneys, but in contrast to 8 is accumulated in the liver [38].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…It is clear that the cluster complex excreted through the kidneys rapidly. Earlier, we have demonstrated that cluster complex 1 can also be excreted through the kidneys, but in contrast to 8 is accumulated in the liver [38].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Indeed, the family of octahedral cluster complexes [{Re 6 Q 8 }L 6 ] and [{Mo 6 X 8 }L 6 ] (where X is Cl, Br or I; Q is S, Se or Te and L are organic or inorganic ligands) and materials based on them have been intensively studied in the last few years in the context of biomedical applications. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] First of all, this is due to the progress made in the develop-ment of phosphorescent octahedral molybdenum cluster complexes, all based on the {Mo 6 I 8 } 4+ cluster core that have particularly high quantum yields [34][35][36][37] and high efficiency in generating singlet oxygen. [38][39][40][41][42][43] Specifically, our recent studies have shown that materials doped using {Mo 6 I 8 } 4+ are highly photoluminescent and have low cellular toxicity in the dark, while by a careful selection of a matrix the cellular internalisation and photoinduced toxicity of the materials can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that hexanuclear rhenium cluster complexes with the general formula [{Re 6 Q 8 }L 6 ] (where Q is S, Se, or Te and Ls are some organic or inorganic apical ligands) have high potential for therapeutic and diagnostic applications in different fields of biology and medicine due to their luminescence, photosensitising and antitumor properties as well as due to highly efficient absorption of X-rays. 1 13 This set of outstanding physical properties led to intensive studies of the biological properties of rhenium octahedral clusters. As an example, we have recently developed the cluster complex Na 2 H 8 [{Re 6 Se 8 }(P(C 2 H 4 CONH 2 )(C 2 H 4 COO) 2 ) 6 ] that demonstrated high radiodensity and high water solubility.…”
Section: Introductionmentioning
confidence: 99%